T908 Polymeric Micelles Improved the Uptake of Sgc8-c Aptamer Probe in Tumor-Bearing Mice: A Co-Association Study between the Probe and Preformed Nanostructures - Romina Castelli; Manuel Ibarra; Ricardo Faccio; Iris Miraballes; Marcelo Fernández; Albertina Moglioni; Pablo Cabral; Hugo Cerecetto; Romina J. Glisoni; Victoria Calzada (MDPI AG, 2021)
Aptamers are oligonucleotides that have the characteristic of recognizing a target with high affinity and specificity. Based on our previous studies, the aptamer probe Sgc8-c-Alexa647 is a promising tool for molecular imaging of PTK7, which is an interesting biomarker in cancer. In order to improve the delivery of this probe as well as create a novel drug delivery nanosystem targeted to the PTK7 receptor, we evaluate the co-association between the probe and preformed nanostructures. In this work, preformed pegylated liposomes (PPL) and linear and branched pristine polymeric micelles (PMs), based on PEO-PPO-PEO triblock copolymers were used: poloxamer F127® and poloxamines T1307® and T908®. For it, Sgc8-c-Alexa647 and its co-association with the different nanostructures was exhaustively analyzed. DLS analysis showed nanometric sizes, and TEM and AFM showed notable differences between free- and co-associated probe. Likewise, all nanosystems were evaluated on A20 lymphoma cell line overexpressing PTK7, and the confocal microscopy images showed distinctness in cellular uptake. Finally, the biodistribution in BALB/c mice bearing lymphoma-tumor and pharmacokinetic study revealed an encouraging profile for T908-probe. All data obtained from this work suggested that PMs and, more specifically T908 ones, are good candidates to improve the pharmacokinetics and the tumor uptake of aptamer-based probes.